Dengue Virus Envelope Protein Domain III Induces Nlrp3 Inflammasome-Dependent NETosis-Mediated Inflammation in Mice - Lien, Te-Sheng; Sun, Der-Shan; Hung, Shih-Che; Wu, Wen-Sheng; Chang, Hsin-Hou (Frontiers in Immunology, 2021)
Abnormal immune responses and cytokine storm are involved in the development of severe dengue, a life-threatening disease with high mortality. Dengue virus-induced neutrophil NETosis response is associated with cytokine storm; while the role of viral factors on the elicitation of excessive inflammation mains unclear. Here we found that treatments of dengue virus envelope protein domain III (EIII), cellular binding moiety of virion, is sufficient to induce neutrophil NETosis processes in vitro and in vivo. Challenges of EIII in inflammasome Nlrp3-/- and Casp1-/- mutant mice resulted in less inflammation and NETosis responses, as compared to the wild type controls. Blockages of EIII-neutrophil interaction using cell-binding competitive inhibitor or selective Nlrp3 inflammasome inhibitors OLT1177 and Z-WHED-FMK are able to suppress EIII-induced NETosis response. These results collectively suggest that Nlrp3 inflammsome is a molecular target for treating dengue-elicited inflammatory pathogenesis.